Soft-sediment deformation: deep-water slope deposits of a back-arc basin (middle Eocene-Oligocene Kirkgecit Formation, Elazig Basin), Eastern Turkey - Koc-Tasgin, Calibe; Altun, Firat (Springer Heidelberg, 2019)
The Kirkgecit Formation (middle Eocene-Oligocene) is exposed in an approximately E-W direction around the city of Elazig, eastern Turkey. This unit represents marly and sandy deep-marine sediments deposited in a slope setting with channels and contain soft-sediment deformation structures (SSDSs). These SSDSs include slump folds, chaotic strata, load casts, flame structures, convolute laminations, clastic dykes, water-escape structures and syn-sedimentary faults. The main underlying deformation processes are liquefaction, fluidization and gravity-induced loading. Some of the SSDS could be interpreted as seismites, which originated due to earthquakes that also triggered high-density mass flows. This interpretation is consistent with the active tectonics in the Elazig back-arc basin. The SSDS in the study area are compared with SSDS in other regions, as well as with SSDS in other marine deposits. In this way, findings obtained from the study area are compared with SSDS at different locations in the marine Kirkgecit Formation around Elazig and with similar structures developed in marine settings worldwide, such as SE Crete and NW Africa.
Keywords: Soft-sediment deformation structures; Deep-water; Slope; Back-arc setting; Elazig Basin; Turkey